1971
DOI: 10.21273/jashs.96.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rootstock and Length of Interstem on Growth of One-Year-Old Apple Plants in Sand Culture1

Abstract: Comparisons were made of MM.111, MM.106 and EM.IX as rootstocks and ‘Red Delicious’ (RD), MM.106 and EM.IX as 1-, 3-, 5- and 7-inch interstems. The dwarfing effects of the rootstocks were greater than those of the interstems. Interstems reduced the growth of most plant parts in direct proportion to the degree of dwarfing of the interstem and there were few significant differences among plants with different interstem lengths. However, plants with interstems of 1 and 3 inches had higher percentage increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1972
1972
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…After 7 growing seasons, interstem trees of 'Oregon Spur Red Delicious' are smaller and less productive than similar trees of 'Em- pire', 'Macspur', and 'Rogers McIntosh'. This is contrary to results which demonstrated that 'Delicious' interstock with 18-cm stempieces of M 9 grew significantly more than did other combinations (5). It appears that because of the upright branching nature and small leaf surface, the spur-type 'Delicious' strain is slow to develop.…”
contrasting
confidence: 74%
“…After 7 growing seasons, interstem trees of 'Oregon Spur Red Delicious' are smaller and less productive than similar trees of 'Em- pire', 'Macspur', and 'Rogers McIntosh'. This is contrary to results which demonstrated that 'Delicious' interstock with 18-cm stempieces of M 9 grew significantly more than did other combinations (5). It appears that because of the upright branching nature and small leaf surface, the spur-type 'Delicious' strain is slow to develop.…”
contrasting
confidence: 74%
“…Sixty plants were harvested each year, so 240 plants were harvested over the 4 years. An analysis o f covariance on the first year's data (7) showed that the initial wt of the plant parts had no significant effect on treatments.…”
Section: Methodsmentioning
confidence: 96%
“…It may also be related to the presence of ample nutrients in the medium. It has been reported that 32p and 45ca were translocated to the scion more slowly from dwarfing rootstocks (3) and that trees with dwarf interstocks accumulated leaf N more slowly than trees with their own stems (7). Optimum levels of nutrients in the root medium may have resulted in an increased uptake and translocation which decreased dwarfing.…”
Section: Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Duncan Multiple Range Test was used to test significance. For more details on the above mentioned work and for growing procedure and harvest the reader is referred to a previous report by the authors (10). After 1 season's growth in the greenhouse, the entire root system of each treatment was weighed and frozen immediately at -20°C, lyophilized, and ground to pass a 60-mesh sieve, for analyses of protein and free amino acids according to the procedures reported by Lasheen (9).…”
Section: Methodsmentioning
confidence: 99%